2018
DOI: 10.5539/gjhs.v10n12p52
|View full text |Cite
|
Sign up to set email alerts
|

Depression As a Strong Prediction of Suicide Risk

Abstract: Suicide happens throughout one’s life and is a serious health problem. World Health Organization (WHO) placed suicidal problem as society health priority. Many things is related to suicide, among others mental disorders like depression, anxiety, alcohol consumption behavior, life pressure experienced, financial problem, personal relation, or so is chronic illness experienced, conflict occurred, disaster, harassment, alienation social demography characteristic. Objective research to identify the risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…This could become a risk factor as previous studies found family support could buffer the psychological problems during the crisis like the pandemic (Chen et al, 2021;Pramukti et al, 2020;Zhu et al, 2021). The current study also aligned with a previous study on suicidal behavior among Indonesian people before the pandemic, whereby people living in urban area had 3.00 times higher suicide risk due to economic stress than people living in non-urban area (Mubasyiroh et al, 2018).…”
supporting
confidence: 88%
See 3 more Smart Citations
“…This could become a risk factor as previous studies found family support could buffer the psychological problems during the crisis like the pandemic (Chen et al, 2021;Pramukti et al, 2020;Zhu et al, 2021). The current study also aligned with a previous study on suicidal behavior among Indonesian people before the pandemic, whereby people living in urban area had 3.00 times higher suicide risk due to economic stress than people living in non-urban area (Mubasyiroh et al, 2018).…”
supporting
confidence: 88%
“…264this study complemented previous studies on suicidal behavior in specific age groups 265 and limited geographical locations in Indonesia before the pandemic(Ahmad & Turnip, 266 2020;Mubasyiroh et al, 2018;Putra et al, 2019). It was found that nearly 40% of 267 participants in this study reported self-harm and suicide ideation.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…Another reason that depression is crucial is that it could lead to suicide. A study in 3 cities in Indonesia showed that people with depression were 11 times more likely to have suicidal thoughts [ 6 ].…”
Section: Introductionmentioning
confidence: 99%